2012
DOI: 10.1177/0267658312437990
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical gender in L2: A production or a real-time processing problem?

Abstract: Mastery of grammatical gender is difficult to achieve in a second language (L2). This study investigates whether persistent difficulty with grammatical gender often observed in the speech of otherwise highly proficient L2 learners is best characterized as a production-specific performance problem, or as difficulty with the retrieval of gender information in real-time language use. In an experimental design that crossed production/comprehension and online/offline tasks, highly proficient L2 learners of Spanish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
263
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 274 publications
(305 citation statements)
references
References 39 publications
35
263
3
4
Order By: Relevance
“…An examination of all of the L2ers' errors involving both a determiner and an adjective (50 out of 1320 responses) revealed that both error types were infrequent, but there were more than twice as many errors of assignment (a total of 35) than errors of agreement (a total of 15). This low incidence of agreement errors was also observed in the study by Grüter et al (2012), although they also found a higher incidence of assignment errors than we did.…”
Section: Examining Morphological Variability In L2 Learnerssupporting
confidence: 89%
See 4 more Smart Citations
“…An examination of all of the L2ers' errors involving both a determiner and an adjective (50 out of 1320 responses) revealed that both error types were infrequent, but there were more than twice as many errors of assignment (a total of 35) than errors of agreement (a total of 15). This low incidence of agreement errors was also observed in the study by Grüter et al (2012), although they also found a higher incidence of assignment errors than we did.…”
Section: Examining Morphological Variability In L2 Learnerssupporting
confidence: 89%
“…We expected gender agreement with these nouns to be more challenging for adult L2ers, based on previous studies (e.g., Foucart and Frenck-Mestre, 2012;Franceschina, 2005;Grüter et al, 2012;Meulman et al, 2016;Montrul et al, 2008;Sabourin, 2003;Sabourin and Stowe, 2008). Experiment 2 used a spot-the-difference task to examine similar dependencies (determiner-noun-adjective number and gender agreement) in elicited spoken production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations